The Effects of Macroprudential Policies on the Performance of Conventional Banks in Indonesia - Adenan Moh.; Haq Mujab Syaiful; Nasir M. Abd.; Soseco Thomas (ECONOMICS)
A resilient banking system in Indonesia is essential to withstand economic fluctuations that have significantly impacted Indonesia, especially during financial crises. To address these challenges, effective macroprudential policies are required to support the development of a high-performance banking sector. This research examines the impact of macroprudential policies on the performance of conventional banks in Indonesia. The research uses time-series data from 2014 to 2023 obtained from the Indonesian Financial Services Authority (OJK) and the Central Bank of Indonesia (BI). The data is analysed using the Vector Autoregression (VAR) method. The variables estimated include macroprudential policy instruments, including the Macroprudential Intermediation Ratio, Countercyclical Capital Buffer, Loan-to-Value ratio, Minimum Statutory Reserves, and Return on Assets. The results of the study found that most macroprudential measures do not have a substantial impact on the performance of conventional banks in Indonesia. Only Minimum Statutory Reserves significantly affect Return on Assets. Additionally, most variables do not exhibit reciprocal relationships. However, some variables display unidirectional effects. Specifically, the Countercyclical Capital Buffer has a significant causal impact on Return on Assets, while Minimum Statutory Reserves also play a notable role in affecting Return on Assets. Moreover, there is a causal relationship between the Macroprudential Intermediation Ratio and Minimum Statutory Reserves, as well as between the Countercyclical Capital Buffer and Minimum Statutory Reserves. The results of this study can contribute to policies in helping regulators formulate strategies to deal with future economic crises by ensuring that existing policies can maintain financial stability.